Two new species of Myrcia (Myrtaceae) from Brazilian Atlantic Forest - Caliari, Claudia Pigatti; Souza, Vinicius Castro; Mazine, Fiorella F. (Phytotaxa, 2016)
Two new species of Myrcia from the Atlantic rainforest in southeastern Brazil, Myrcia congestiflora and Myrcia longipaniculata are here described and illustrated. Myrcia congestiflora occurs in São Paulo and Rio de Janeiro states and is similar to Myrcia cerqueiria, differing by having densely sericeous indumentum (versus sparse and shorter trichomes), larger flowers and flower buds (flower buds with 3–4 mm versus 1.1 mm long) and by acute or obtuse calyx lobes rather than rounded. Myrcia longipaniculata is known for one collection from the boundary of São Paulo and Rio de Janeiro differing from Myrcia spectabilis mainly by the longer inflorescence size (29 cm versus 3.5–21.5 cm long.) as well as for presenting a strong reddish or ferruginous indumentum (versus brown to yellowish).